Heart team consultations for patients with severe coronary artery disease or valvular heart disease in the era of the COVID-19 pandemic: a single-center experience - Jonik, Szymon; Boszko, Maria; Sztemberg, Elena; Łepecki, Dominik; Grodziński, Bartłomiej; Mikusek-Pham Van, Marcin; Marchel, Michał; Kochman, Janusz; Kuśmierczyk, Mariusz; Opolski, Grzegorz; Grabowski, Marcin; Mazurek, Tomasz (Frontiers in Cardiovascular Medicine, 2023)
The Heart Team (HT) as group of experienced specialists is responsible for optimal decisions making for high-risk cardiac patients. The aim of this study was to investigate the impact of COVID-19 pandemic on HT functioning.In this retrospective, single-center study we evaluated the cooperation of HT in terms of the frequency of meetings, the number of consulted patients and the trends in choosing the optimal treatment strategies for complex individuals with severe coronary artery disease (CAD) or valvular heart disease (VHD) before and during COVID-19 pandemic in Poland.